A new European investor sentiment index (EURsent) and its return and volatility predictability - Reis, Pedro Manuel Nogueira (2020)
This study presents a new European investor sentiment index, EURsent, based on new individual sentiment proxies such as VSTOXX, gold, and the German bond yield spread, and studies the spillover and contagion between the United States and Europe. Furthermore, it analyses the simultaneous influence of this new sentiment measure index on both volatility and stock returns, including causality. Applying well-established statistical techniques, such as principal component analysis, ordinary least squares, autoregressive conditional heteroskedasticity (ARCH), generalized ARCH (GARCH), and threshold GARCH models, the findings demonstrate how EURsent is closely interrelated with the most universally recognized sentiment index in academia, demonstrating strong co-movement between the US and European stock markets, mainly prior to the global subprime crisis. The study also applies vector autoregressive modelling and OOS analysis that allows one to conclude that EURsent is a strong predictor of market returns, through the discount rate and cash flow news, although the latter is the most relevant channel. This study creates a truly representative measure of global European investor sentiment that is comparable to that created by Baker and Wurgler for the United States, interlinking a holistic sentiment measure index, sustained on new single investor sentiment proxies, with conditionally market volatility and market returns, suggesting causality. EURsent could thus be a tool for investment managers, investors, and financial service providers as well as regulators to monitor the evolution of stock markets.